DAMPAK PERUBAHAN NILAI-NILAI HUKUM DALAM MASYARAKAT TRADISIONAL DAN MODERN - Muhammad Surya Bimantoro; Kamaruddin; Arifai (Journal Publicuho, 2024)
This study aims to determine the impact of changes in legal values ​​in traditional and modern societies. This type of research uses a legal research type. The approach methods used in this study are the Statute Approach, Conceptual Approach, and Case Approach with primary and secondary legal materials with perspective analysis techniques. (Peter Mahmud, 2008:93). The results of the study show that the transformation of values ​​from traditional to modern societies has a significant impact on social stability, family relationships, and social interactions. Traditional values ​​such as mutual cooperation and obedience to parents maintain harmony and solidarity, while the shift to individualistic values ​​in modern society tends to reduce community involvement and weaken family social support, so strategies are needed to support social and emotional well-being in modern society.